2020
DOI: 10.14260/jemds/2020/165
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Variations and Treatment Responses of Catatonic Patients in the Psychiatric In-Patient Department of a Rural Tertiary Care Centre - A Clinical Study from Eastern India

Abstract: A B S T R A C T BACKGROUNDThere are very few studies regarding diagnostic variations and treatment response in catatonia in India. We wanted to assess the treatment response according to the background psychiatric diagnoses of in-patient catatonic patients. METHODSThis is a cross-sectional descriptive study done in the Psychiatric indoor of North Bengal Medical College between December 2018 to December 2019. Catatonia was diagnosed using DSM-5 criteria in the patients admitted. A total 30 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…13,14,16,17,24 Although it is often argued that over long-term observation, sometimes, the diagnosis of brief psychosis and unspecified psychosis can be changed into affective disorders. 36 Apart from the psychotic spectrum, affective, conversion, and substance use, and organic etiologies were also found albeit at the lower proportions. Studies based on similar age range found almost similar distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,16,17,24 Although it is often argued that over long-term observation, sometimes, the diagnosis of brief psychosis and unspecified psychosis can be changed into affective disorders. 36 Apart from the psychotic spectrum, affective, conversion, and substance use, and organic etiologies were also found albeit at the lower proportions. Studies based on similar age range found almost similar distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies conducted among children and adolescents as well as among persons of mixed age range found a varying proportion of lorazepam response from 50% to 85%. [13][14][15][16][17]24,25,36 The varying rate of response in different studies can be attributed to delay in presentation to treatment facilities as well as the duration of untreated illness. 32 In this case, prolonged lorazepam treatment due to difficulty to pursue ECT protocol during pandemic could be one contributory reason as well.…”
Section: Discussionmentioning
confidence: 99%